How to improve adherence of guidelines for localized testicular cancer surveillance: A Delphi consensus study - Da Silva, Angélique; Fléchon, Aude; Coquan, Elodie; Planchamp, François; Culine, Stéphane; Murez, Thibaut; Méjean, Arnaud; Pasquier, David; Chevreau, Christine; Fizazi, Karim; Thiery-Vuilemin, Antoine; Joly, Florence (Frontiers in Oncology, 2022)
Stage-I testicular germ-cell tumor (TGCT) has excellent cure rates. Surveillance is fully included in patient’s management, particularly during the first years of follow-up. Surveillance guidelines differ between the academic societies, mainly concerning imaging frequency and long-term follow-up. We evaluated surveillance practice and schedules followed by French specialists and set up a DELPHI method to obtain a consensual surveillance program with an optimal schedule for patients with localized TGCT. First, an online survey on surveillance practice of stage-I TGCT based on clinical-cases was conducted among urologists, radiation-oncologists and medical-oncologists. These results were compared to ESMO/EAU and AFU guidelines. Then a panel of experts assessed surveillance proposals following a Delphi-CM. Statements were drafted after analysis of the previous survey and systematic literature review, with 2 successive rounds to reach a consensus. The study was conducted between July 2018 and May 2019. Concerning the first step : 61 participated to the survey (69% medical-oncologists, 15% urologists, 16% radiation-oncologists). About 65% of practitioners followed clinico-biological guidelines concerning 1 to 5 years of follow-up, but only 25% stopped surveillance after the 5th-year. No physician followed the EAU/ESMO guidelines of de-escalation chest imaging. Concerning the second step : 32 experts (78% medical-oncologists, 16% urologists, 6% radiation-oncologists) participated to the Delphi-CM. Thanks to Delphi-CM, a consensus was reached for 26 of the 38 statements. Experts agreed on clinico-biological surveillance modalities and end of surveillance after the 5th-year of follow-up. For seminoma, abdominal ultrasound was proposed as an option to the abdominopelvic (AP) scan for the 4th-year of follow-up. No consensus was reached regarding de-escalation of chest imaging. To conclude, the survey proved that French TGCT-specialists do not follow current guidelines. With Delphi-CM, a consensus was obtained for frequency of clinico-biological surveillance, discontinuation of surveillance after the 5th-year, stop of AP scan on the 4th-year of follow-up for seminoma. Questions remains concerning type and frequency of chest imaging.